2004
DOI: 10.1002/ijc.20327
|View full text |Cite
|
Sign up to set email alerts
|

Amount of DNA in plasma and cancer risk: A prospective study

Abstract: Levels of plasma DNA concentrations in cancer patients have been shown to be higher than the plasma DNA concentrations found in healthy subjects. The value of plasma DNA levels for development of neoplastic or pulmonary disease was evaluated in a large prospective study. Plasma samples (n ‫؍‬ 1,184) were analyzed from 776 controls, 359 cases of cancer (lung, bladder, oral cavity, pharynx, larynx, leukemia) and 49 deaths from chronic obstructive pulmonary disease (COPD), including never smokers and ex-smokers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 8 publications
7
61
0
2
Order By: Relevance
“…This contradicts the observations of Jung et al [28], who reported that the DNA concentration in plasma did not change when blood samples were stored at RT for 8 h, or at 4 o C for 24 h. These contradictory results might be due to sampling at only two time points (8 and 24 h) at 4 o C in their study. It is likely that the increased DNA levels found at 25h are attributable to contamination of plasma with genomic DNA from leukocyte lysis [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This contradicts the observations of Jung et al [28], who reported that the DNA concentration in plasma did not change when blood samples were stored at RT for 8 h, or at 4 o C for 24 h. These contradictory results might be due to sampling at only two time points (8 and 24 h) at 4 o C in their study. It is likely that the increased DNA levels found at 25h are attributable to contamination of plasma with genomic DNA from leukocyte lysis [3].…”
Section: Discussionmentioning
confidence: 99%
“…It is present in normal healthy individuals at low concentrations (ng/ml) [3]. Raised levels of CFDNA in cancer patients have been reported in many tunour types [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that cancer patients have higher cfDNA levels than healthy donors, however, the overall concentration of cfDNA varies considerably in blood samples in both groups [19][20][21][22][23]. An average of 180 ng cfDNA per mL of blood has been measured in cancer patients, whereas healthy individuals carry about 30 ng of cfDNA per mL of blood [24].…”
Section: Defining Circulating Cell Free Dna and Approaches To Liquid mentioning
confidence: 99%
“…An average of 180 ng cfDNA per mL of blood has been measured in cancer patients, whereas healthy individuals carry about 30 ng of cfDNA per mL of blood [24]. A prospective study of cell-free DNA levels in plasma samples and their impact in cancer patients showed considerable variation between the European Prospective Investigation into Cancer and Nutrition (EPIC) centers [23]. It was discussed that this individual variation ( Figure 1) was due to the type of population and the treatment of samples.…”
Section: Defining Circulating Cell Free Dna and Approaches To Liquid mentioning
confidence: 99%